The Effects of Powder Recycling on the Mechanical Properties of Laser Powder Bed Fusion Stainless Steel for Nuclear Applications - RORY DOUGLAS (2024)
Laser powder bed fusion (L-PBF) is a form of additive manufacturing (AM) that can be used to manufacture geometrically complex parts in near net shapes. This form of manufacturing lends itself to high performance engineering parts, which are required in small to medium quantities. As such, L-PBF of 316L stainless steel has been adopted by Rolls-Royce for the manufacture of components for use in pressurised water reactors (PWR). With L-PBF being used to manufacture parts, optimising and controlling the method of production is paramount.Powder recycling refers to the reuse of the powder feedstock in L-PBF across multiple builds and is crucial for the economic viability of L-PBF. However, through powder recycling, the physical and chemical properties of powder are liable to change. This variation in powder properties could lead to knock-on effects for the mechanical properties of parts.This study begins by identifying the changes that occur to powder as a result of recycling. This includes changes to powder size distribution (PSD), flowability, chemistry, porosity and phase composition of recycled powder. The uniaxial tensile and low cycle fatigue (LCF) performance of parts manufactured at different levels of powder recycling were investigated, complimented by thorough microstructural, chemical and porosity analysis. Finally, other sources of variation in the LCF performance of L-PBF 316L were studied. This was undertaken to weigh the relative importance of powder recycling against other variables such as intermachine variability, altering build parameters and post manufacture heat treatment of parts.Although moderate changes to powder were observed as a result of recycling, this was found to not result in any negative changes to part performance. In addition, the microstructure of 316L remained stable across differing levels of powder recycling. Porosity increased marginally as the fine particle content of powder was reduced, but this was not sufficient to affect the low cycle fatigue performance of parts. After powder recycling, variations to ductility and Young’s modulus were primarily attributed to the small specimen geometry tested. The optimal recommendation for controlling powder recycling was derived to include strict controls over the initial virgin powder condition. More important factors to consider when monitoring the properties of production L-PBF 316L parts included build parameters, post process HT and sample orientation. Variations to all three of these factors resulted in microstructural change within L-PBF 316L, which created more significant variation within part properties in comparison to powder recycling.